Medicaid Beneficiaries' Access to Residential Care Settings. Issue 4 (2nd October 2017) - Lepore, Michael; Knowles, Molly; Porter, Kristie A.; O'Keeffe, Janet; Wiener, Joshua
ABSTRACT: Residential care settings (RCSs) are community-based housing and supportive services providers. Medicaid beneficiaries' access to RCSs is of concern to policymakers and other stakeholders because most people prefer community-based to institutional services and RCSs are generally less expensive than nursing homes. To better understand Medicaid beneficiaries' access to state-licensed RCSs, we examined Medicaid policies in 50 states and the District of Columbia, interviewed seven subject-matter experts, and conducted four state case studies informed by reviews of state policies and interviews with 27 stakeholders. Factors identified as influencing Medicaid beneficiaries' access to RCSs include Medicaid reimbursement rates for RCS services, the supply of Medicaid-certified RCSs and RCS beds, and policies that affect RCS room and board costs for Medicaid beneficiaries. Shifting Medicaid spending toward community-based instead of institutional care may require attention to these interrelated issues of RCS payment, supply, and room and board costs.